Tracking mobile terminals in wireless networks - Kyamakya, Kyandoghere; Khalaf-Allah, Mohamed (2007 International Waveform Diversity and Design Conference, WDD, 2007)
We propose a Bayesian filter algorithm for tracking the position of mobile terminals in wireless cellular networks when the loss of GPS information occurs. Our technique utilizes simulated IMU (inertial measurement unit) data and map-matching according to the received cell-ID in the prediction and update steps of the algorithm respectively. The map used for matching has been generated by correlating geographical data and radio profile prediction information of the experimental area. We show how to maintain location information for mobile terminals in wireless networks using a novel combination of data sources. Our approach provides a reliable solution in street canyons and heavy tree canopies where GPS information is almost always inapplicable. The developed technique could also be applied to vehicle navigation, where dead-reckoning instruments are available and accurate. ©2007 IEEE.
Created from Fastlane, Scopus look-up